Food at Home and away from Home: Commodity Composition, Nutrition Differences, and Differences in Consumers. (August 2019) - Binkley, James K.; Liu, Yuhang
Abstract : Food away from home (FAFH) accounts for over 40 percent of food spending. We use NHANES survey data to examine resulting effects on commodity sectors, and find that production/consumption of beef, chicken, potatoes, cheese, and lettuce have increased the most due to FAFH, while fluid milk and all fruits have declined. Such changes have reduced overall nutrition, and nutrition within commodity categories is generally lower in restaurants than at home. FAFH consumers tend to have less healthy home diets than have nonconsumers, suggesting that observed low FAFH nutrition may be partly because restaurant diners select less healthy foods regardless of source.